ali48
ali48
16-07-2017
Mathematics
contestada
F(x) =x^2+6x and g(x)=7-x find (f-g)(x) and (f-g)(9)
Respuesta :
Nick911
Nick911
16-07-2017
f(x)=x²+6x
g(x)=7-x
(f-g)(x) means that f(x)-g(x), so
f(x)-g(x)
=x²+6x-7+x
Combining like terms
x²+6x+x-7
=x²+7x-7, so (f-g)(x)=x²+7x-7
Next,
(f-g)(x)
=x²+7x-7
(f-g)(9)
=(9)²+7(9)-7
=81+63-7
=144-7
=137, so (f-g)(9)=137. Hope it help!
Answer Link
VER TODAS LAS RESPUESTAS ( 19+ )
Otras preguntas
Which quotation was most likely made by an absolute monarch?1) "the government that governs best, governs least."2) "i am the state"3) "the government must be p
A store manager did a study to determine the amount of money the first 50 customers spent in her store. The data are approximately normally distributed with a m
Which can be determined using a chemical formula? a. the elements that make up the compound b. the substances that make up a solution c. the pH of a solution
You see a magazine ad for face soap. It states that eight out of 10 teenagers prefer their soap. It claims to be 25 percent more effective against acne. It incl
what is the difference between a period and a group on the periodic table
Match each excerpt from H. G. Wells's The Time Machine with the theme it expresses. humankind and nature good versus evil horrors of science evolution society a
Which sentence from Shakespeare's Julius Caesar uses the same literary technique that is used in these lines? You Blockes, you stones, you worse then senslesse
Choose the paragraph that uses indirect characterization. A. Lisa was confident and beautiful. With her gorgeous auburn locks and perfect figure, she looked stu
What is 9.05 × 105 written in standard form?
In his study of pea plants, Gregor Mendel used which method to produce offspring?
ACCESS MORE